2018
DOI: 10.1039/c8ce00120k
|View full text |Cite
|
Sign up to set email alerts
|

Lead-carboxylate/polyiodide hybrids constructed from halogen bonding and asymmetric viologen: structures, visible-light-driven photocatalytic properties and enhanced photocurrent responses

Abstract: Two lead-carboxylate/polyiodide hybrids constructed from halogen bonding and asymmetric viologen have been synthesized, which exhibit efficient photocatalytic degeneration performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Photocurrent generation has been observed in metal halide based hybrids , . Photoelectrochemical experiments have also been performed on 1 , 3 and 4 according to typical method.…”
Section: Resultsmentioning
confidence: 99%
“…Photocurrent generation has been observed in metal halide based hybrids , . Photoelectrochemical experiments have also been performed on 1 , 3 and 4 according to typical method.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CPs have attracted increasing attention in the recent years. [25][26][27][28][29][30][31] It was found that the adsorption of I 2 by crystalline porous materials, including CPs, was based on noncovalent interactions like halogen bonding interactions between I 2 and Lewis basic sites [32][33][34][35] or charge-transfer interactions between the electron-poor I 2 and π-electron rich aromatics. [36][37][38][39][40][41] Thus, a combination of halogen bond and CT interactions between the guest I 2 molecules and the host frameworks imparts a comprehensive tuning effect on the iodine capture process.…”
Section: Introductionmentioning
confidence: 99%
“…But after loading with (DEAST)I, their currents decrease greatly (0.72×10 −7 A for (DEAST)I@La‐LMOC, 0.63×10 −7 A for (DEAST)I@Nd‐LMOC). According to universal accepted photocurrent generation mechanism, radicals on organic moiety can generate under irradiation, then the electrons on organic moiety move to ITO substrates to produce the recyclable currents . In this work, for Ln‐LMOC, radicals can appear on BTB to produce BTB .…”
Section: Resultsmentioning
confidence: 87%
“…According to universal accepted photocurrent generation mechanism,r adicals on organic moiety can generate under irradiation, then the electrons on organic moiety move to ITO substrates to produce the recyclable currents. [34] In this work, for Ln-LMOC,r adicals can appear on BTB to produce BTBC radicals, and electron-rich Ln 2 O 16 dimers can transfer their electrons to BTBC radicals. Because there are covalently bonded between the radicalc enters and electron-rich Ln 2 O 16 units, this electront ransfer is smooth.…”
Section: Photocurrent Responsep Erformancesmentioning
confidence: 81%